# SOLUTION: how do i factor 6x^3 + 15x^2 + -9x

Algebra ->  -> SOLUTION: how do i factor 6x^3 + 15x^2 + -9x      Log On

 Ad: Mathway solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

Question 645131: how do i factor 6x^3 + 15x^2 + -9x
Found 3 solutions by jim_thompson5910, stanbon, MathLover1:
You can put this solution on YOUR website!
Note:

6x^3 + 15x^2 + -9x

is the same as

6x^3 + 15x^2 - 9x

Factor out the GCF .

Now let's try to factor the inner expression

---------------------------------------------------------------

Looking at the expression , we can see that the first coefficient is , the second coefficient is , and the last term is .

Now multiply the first coefficient by the last term to get .

Now the question is: what two whole numbers multiply to (the previous product) and add to the second coefficient ?

To find these two numbers, we need to list all of the factors of (the previous product).

Factors of :
1,2,3,6
-1,-2,-3,-6

Note: list the negative of each factor. This will allow us to find all possible combinations.

These factors pair up and multiply to .
1*(-6) = -6
2*(-3) = -6
(-1)*(6) = -6
(-2)*(3) = -6

Now let's add up each pair of factors to see if one pair adds to the middle coefficient :

First NumberSecond NumberSum
1-61+(-6)=-5
2-32+(-3)=-1
-16-1+6=5
-23-2+3=1

From the table, we can see that the two numbers and add to (the middle coefficient).

So the two numbers and both multiply to and add to

Now replace the middle term with . Remember, and add to . So this shows us that .

Replace the second term with .

Group the terms into two pairs.

Factor out the GCF from the first group.

Factor out from the second group. The goal of this step is to make the terms in the second parenthesis equal to the terms in the first parenthesis.

Combine like terms. Or factor out the common term

--------------------------------------------------

So then factors further to

===============================================================

So completely factors to .

In other words, for all values of x.

Note: you can check the answer by expanding to get or by graphing the original expression and the answer (the two graphs should be identical).

--------------------------------------------------------------------------------------------------------------
If you need more help, email me at jim_thompson5910@hotmail.com

Also, please consider visiting my website: http://www.freewebs.com/jimthompson5910/home.html and making a donation. Thank you

Jim
--------------------------------------------------------------------------------------------------------------

You can put this solution on YOUR website!
factor 6x^3 + 15x^2 + -9x
-------
= 3x(2x^2 + 5x -3)
---
= 3x(2x^2 -x+6x -3)
------
= 3x(x(2x-1)+3(2x-1))
----
= 3x(2x-1)(x+3)
=====================
Cheers,
Stan H.